2017
DOI: 10.1002/cctc.201701629
|View full text |Cite
|
Sign up to set email alerts
|

Nonprecious‐metal Fe/N/C Catalysts Prepared from π‐Expanded Fe Salen Precursors toward an Efficient Oxygen Reduction Reaction

Abstract: Non‐precious metal electrocatalysts are under investigation as alternatives to platinum‐group metal electrocatalysts for the oxygen reduction reaction (ORR), which is required for cathode materials in fuel cells. Herein, we describe a new method for the synthesis of metal and nitrogen‐containing carbon (M/N/C) catalysts with high ORR activity using π‐expanded Fe(Salen) precursors. The Fe/N/C ORR catalysts were obtained by pyrolysis of a mixture of carbon support (Vulcan XC‐72R) and the iron complex precursors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…In addition, the XANES spectrum at the Fe K-edge of the catalyst calcinated at 800°C is shown in figure 8d. The pre-edge and edge features of the catalyst are clearly different from those of Fe-foil, Fe(II) Phthalocyanine, FeO, Fe 3 O 4 and α-Fe 2 O 3 , while the shape matches well with that of Fe 3 C shown in a previous report [28]. This trend is corresponding to the result of XRD.…”
Section: (B) Effects Of the Temperature Of Second Carbonization Process On Oxygen Reduction Reaction Activitysupporting
confidence: 75%
“…In addition, the XANES spectrum at the Fe K-edge of the catalyst calcinated at 800°C is shown in figure 8d. The pre-edge and edge features of the catalyst are clearly different from those of Fe-foil, Fe(II) Phthalocyanine, FeO, Fe 3 O 4 and α-Fe 2 O 3 , while the shape matches well with that of Fe 3 C shown in a previous report [28]. This trend is corresponding to the result of XRD.…”
Section: (B) Effects Of the Temperature Of Second Carbonization Process On Oxygen Reduction Reaction Activitysupporting
confidence: 75%
“…In particular, Fe/2NAPD@VC has a signicantly shied onset potential, suggesting that introduction of aromatic rings into the ligand framework of the precursor positively shis the onset potential in Fe/2NAPD@VC relative to Fe/salen@VC. 36 Among the M/N/C catalysts prepared in this work, Fe/2NAPD@VC has the most shied positive onset potentials (0.82 V) relative to the onset potentials of other catalysts including Cu/2NAPD@VC, Co/ 2NAPD@VC, Ni/2NAPD@VC, and Mn/2NAPD@VC (Table 1). The average number of electrons transferred during O 2 reduction is 3.6 for Fe/2NAPD@VC, generally indicating occurrence of four electron reduction.…”
Section: Orr Activitymentioning
confidence: 82%
“…[33][34][35] Previously, we reported preparation of Fe/N/C catalysts having high ORR activity by systematically tuning an aromatic framework of Fe(salen) complex precursors. 36 We demonstrated that the designed Fe(salen) derivatives with various aromatic moieties such as 1NAPD and 2NAPD ligands have higher thermal stability, which affects the annulation process of the complexes during pyrolysis, thereby leading to higher ORR activity. In this work, we describe preparation and characterization of new bimetallic FeM/N/C catalysts via pyrolysis of the p-expanded metal salen complexes M(2NAPD) and measurement of their ORR activity.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, it can be seen from the diagram that all the polarization curves have two distinct potential regions, that is a mixed dynamic/diffusion controlled area between 0.6 and 0.8 V and a distinct diffusion controlled region (<0.6 V) (Tanaka et al, 2018). Moreover, for the Fe-PIPhen/C catalyst, the ORR onset potential ( E onset ) and the limiting diffusion current density (I ldc ) are 0.85 V and 4.4 mA/cm 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%